Effect of an additional hydrophilic versus hydrophobic coat on the quality of dentinal sealing provided by two-step etchand-rinse adhesives (Journal of Applied Oral Science, 2009)
OBJECTIVE: To test the hypothesis that the quality of the dentinal sealing provided by two-step etch-and-rinse adhesives cannot be altered by the addition of an extra layer of the respective adhesive or the application of a more hydrophobic, non-solvated resin. MATERIAL AND METHODS: full-crown preparations were acid-etched with phosphoric acid for 15 s and bonded with Adper Single Bond (3M ESPE), Excite DSC (Ivoclar/Vivadent) or Prime & Bond NT (Dentsply). The adhesives were used according to the manufacturers' instructions (control groups) or after application to dentin they were a) covered with an extra coat of each respective system or b) coated with a non-solvated bonding agent (Adper Scotchbond Multi-Purpose Adhesive, 3M ESPE). Fluid flow rate was measured before and after dentin surfaces were acid-etched and bonded with adhesives. RESULTS: None of the adhesives or experimental treatments was capable to block completely the fluid transudation across the treated dentin. Application of an extra coat of the adhesive did not reduce the fluid flow rate of adhesive-bonded dentin (p>;0.05). Conversely, the application of a more hydrophobic non-solvated resin resulted in significant reductions in the fluid flow rate (p